Balance of XYL1 and XYL2 expression in different yeast chassis for improved xylose fermentation - Zha, Jian; Hu, Menglong; Shen, Minghua; Li, Bingzhi; Wang, Jingyu; Yuan, Yingjin (Frontiers in Microbiology, 2012)
Reducing xylitol formation is an important step in engineering xylose reductase/xylitol dehydrogenase pathway for ethanol production from xylose in Saccharomyces cerevisiae. In this study, to balance the expression of XYL1 and mutant XYL2 encoding xylose reductase and NADP+-preferring xylitol dehydrogenase for reduced xylitol production, we utilized a strategy combining chassis selection and direct fine-tuning of XYL1 and XYL2 expression. A XYL1 gene under control of various promoters of ADH1, truncated ADH1 and PGK1, and a mutated XYL2 with different copy numbers were constructed into different xylose-utilizing modules, which were then expressed in two yeast chassis W303a and L2612. The strategy enabled us to achieve an improved L2612-derived recombinant strain with XYL1 controlled by promoter PGK1 and with two copies of XYL2. The strain exhibited 21.3% lower xylitol yield and 40.0% higher ethanol yield. The results demonstrate the feasibility of the combinatorial strategy for construction of efficient xylose-fermenting Saccharomyces cerevisiae.